2021
DOI: 10.48550/arxiv.2111.13230
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

FedDropoutAvg: Generalizable federated learning for histopathology image classification

Abstract: Federated learning (FL) enables collaborative learning of a deep learning model without sharing the data of participating sites. FL in medical image analysis tasks is relatively new and open for enhancements. In this study, we propose FedDropoutAvg, a new federated learning approach for training a generalizable model. The proposed method takes advantage of randomness, both in client selection and also in federated averaging process. We compare FedDropoutAvg to several algorithms in an FL scenario for real-worl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Differentially private federated learning is proposed as a potential technique for learning from distributed medical data, such as histopathology scans [112][113][114]. Federated learning enables the training of models without openly disclosing patient information, reducing privacy and confidentiality concerns related to healthcare data [115].…”
Section: Data Privacy Improvementmentioning
confidence: 99%
“…Differentially private federated learning is proposed as a potential technique for learning from distributed medical data, such as histopathology scans [112][113][114]. Federated learning enables the training of models without openly disclosing patient information, reducing privacy and confidentiality concerns related to healthcare data [115].…”
Section: Data Privacy Improvementmentioning
confidence: 99%
“…The first two strategies are part of one of the initial studies done on FL and serve as the standard baseline for FL strategies. The remaining three were chosen as they have often been mentioned and used as benchmarks for multiple studies [29][30][31][32]. FedAvg aggregates the clients' weights by performing a weighted average to generate the new global model.…”
Section: Federated Setupmentioning
confidence: 99%
“…They also prevent data leakage by not sharing the statistics of the collaborator-specific layer activations and benchmarked the model on Camelyon 16 and Camelyon 17 breast cancer datasets [11]. Gunesli et al [12] proposed FedDropoutAvg which is a novel FL model aggregation method inspired from the well-known DL regularization DropOut method and benchmarked this proposed method on the CRC dataset of TCGA portal. It is reported that the FedDropOutAvg method reached to the closest level of centralized training compared to the FedProx and FedAvg [12].…”
Section: Fl Applications On Cpmentioning
confidence: 99%
“…Gunesli et al [12] proposed FedDropoutAvg which is a novel FL model aggregation method inspired from the well-known DL regularization DropOut method and benchmarked this proposed method on the CRC dataset of TCGA portal. It is reported that the FedDropOutAvg method reached to the closest level of centralized training compared to the FedProx and FedAvg [12].…”
Section: Fl Applications On Cpmentioning
confidence: 99%